Psychosocial Determinants of Adequacy of Gestational Weight Gain - Best, Jennifer L. (2008)
Pregnancy is a critical time window for evaluating weight gain on subsequent risk for obesity among women of childbearing age. The purpose of this investigation was to determine if symptoms of depression, anxiety, stress, self-esteem and fetal health locus of control beliefs were significant risk factors for adequacy of gestational weight gain (GWG) when maternal sociodemographic characteristics and health behaviors were considered. Sixteen hundred and five women were prospectively followed from ≤20 weeks’ gestation through delivery. Participants completed standard self-report questionnaires. Adequacy of GWG was expressed as the ratio of observed/expected weight gain based on Institute of Medicine recommendations. Multivariate ANOVA models were conducted and generalized linear models were performed to calculate risk ratios.. Higher depressive symptoms reported throughout pregnancy were significantly associated with higher adequacy ratios. Stronger beliefs in chance in determining fetal health predicted inadequate relative to adequate GWG and was positively associated with larger GWG ratios overall. Several relationships were attenuated when adjusted for covariates. The relationship between psychosocial status and adequacy of GWG is significantly impacted by maternal sociodemographic factors and health practices engaged in during pregnancy. Women who tend to believe that external factors primarily determine fetal health appear to be more vulnerable to non-adherence to clinical GWG guidelines. These results have important implications for targeting prevention and intervention efforts for improving maternal and fetal outcomes secondary to GWG patterns